Awareness of the implementation of the Falsified Medicines Directive among pharmaceutical companies' professionals in the European Economic Area - Włodarczak U; Swieczkowski D; Religioni U; Jaguszewski M; Krysinski J; Merks P. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: The Falsified Medicines Directive (FMD) is a response of the European Union to the increasing number of falsified medicines present in the legal supply chain within the Member States of the community. Effective implementation of the new regulations will depend on the effective cooperation of all parties involved in the distribution of medicinal products including the managers of pharmaceutical companies. Objective: The objective of the study was to examine awareness of the Implementation of the FMD among pharmaceutical company professionals in the European Economic Area. Methods: Sampling was conducted using a method called purposive sampling. An appropriate research tool in the form of an original questionnaire was made available to the respondents in electronic form. During the period from January 2016 to June 2016, 1,496 e-mail messages were sent. The response rate was 17.37%. Results: The study included 99 women (39.3%) and 153 men (60.7%). In the study group, 95.7% of people had heard of FMD. Doctors had rarely heard about the falsified medicine directive when compared to pharmacists (p=0.0063), people working in the pharmaceutical industry (p=0.0014), and respondents with a different professional profile (p=0.0114). In the study group, 89.6% of people were aware of the role of National Medicines Verification Organization in the process of implementing the provisions of FMD into the national system of distribution of medicinal products. The number of the respondents who knew the deadline for the implementation of FMD was significantly higher in the study population, i.e. 91.9% (p=0.0001). Both the younger respondents and those with lower level of education were less aware of the time requirements posed to national regulators (p=0.0003, p=0.0023, respectively). Conclusions: Awareness of the regulations related to the implementation of the FMD, although relatively high among pharmaceutical company professionals in the EEA, is still insufficient.